Disparity between dorsal and ventral networks in patients with obsessive-compulsive disorder: evidence revealed by graph theoretical analysis based on cortical thickness from MRI - Kim, Seung-Goo; Jung, Wi Hoon; Kim, Sung Nyun; Jang, Joon Hwan; Kwon, Jun Soo (Frontiers in Human Neuroscience, 2013)
As one of the most widely accepted neuroanatomical models on OCD, it has been hypothesized that imbalance between an excitatory direct (ventral) pathway and an inhibitory indirect (dorsal) pathway in cortico-striato-thalamic circuit underlies the emergence of OCD. Here we examine the structural network in drug-free patients with OCD in terms of graph theoretical measures for the first time. We used a measure called efficiency which quantifies how a node transfers information efficiently. To construct brain networks, cortical thickness was automatically estimated using T1-weighted magnetic resonance imaging. We found that the network of the OCD patients was as efficient as that of healthy controls so that the both networks were in the small-world regime. More importantly, however, disparity between the dorsal and the ventral networks in the OCD patients was found, suggesting a positive evidence to the imbalance theory on the underlying pathophysiology of OCD.